Metal ion doped manganese-based composite catalyst as well as preparation method and application thereof

By doping metal ions into MnO2 in the ε crystal form, a metal ion-doped manganese-based composite catalyst was prepared, which solved the problem of poor long-term stability of existing Mn-based catalysts and achieved efficient and stable ozone decomposition performance.

CN119406402APending Publication Date: 2025-02-11JIANGSU UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411520454.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing Mn-based catalysts have problems of poor long-term stability and easy deactivation in the field of ozone decomposition, and it is difficult to effectively reduce the ozone concentration.

Method used

Using a metal ion-doped manganese-based composite catalyst, a catalyst with excellent long-term stability and high-efficiency ozone decomposition performance is prepared by doping metal ions such as nickel, cobalt, potassium, sodium, and lithium into the ε crystalline MnO2.

Benefits of technology

The long-term stability and efficient ozone decomposition performance of the catalyst were achieved, especially at 30°C and 60% relative humidity conditions, the decomposition efficiency of 50ppm ozone was close to 100%, and it showed excellent performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406402A_ABST
    Figure CN119406402A_ABST
Patent Text Reader

Abstract

The invention discloses a metal ion doped manganese-based composite catalyst as well as a preparation method and application thereof. The catalyst is metal ion doped MnO2 in an epsilon crystal form; wherein the metal ion is any one of nickel, cobalt, potassium, sodium and lithium; and in the catalyst, the molar ratio of the manganese element to the metal ions is (1-3): 1. The obtained manganese-based composite catalyst has excellent long-term stability, is not easy to inactivate, shows excellent performance in various severe environments, and is very suitable for ozonolysis in the atmospheric environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal ion-doped manganese-based composite catalyst and a preparation method and application thereof, belonging to the technical field of ozone catalytic decomposition. Background Art

[0002] Ozone, as an atmospheric pollutant, has now attracted widespread attention. The sources of ozone are mainly divided into natural sources and anthropogenic sources. Natural sources of ozone mainly come from the atmosphere at an altitude of 10 km to 50 km; anthropogenic sources are mainly photochemical smog produced by nitrogen oxides (NOx) and volatile organic compounds (VOCs) under light conditions. In addition, ozone is also used in food preservation and sewage treatment. Studies have shown that humans will develop serious respiratory diseases if they are in an ozone environment for a long time. At the same time, ozone can also irritate human eyes and damage the central nervous system. Ozone can also reduce the chlorophyll concentration of plants, affect their photosynthesis, and thus lead to reduced crop yields. Therefore, it is crucial to reduce the ozone concentration in people's living environment. Catalytic decomposition technology is now the main means of removing ozone. Among them, Mn-based catalysts are widely used in the field of ozone decomposition due to their diverse oxidation states, high activity, and low price. However, their long-term stability is poor and the problem of easy deactivation has not been well solved. Summary of the invention

[0003] The object of the present invention is to provide a metal ion-doped manganese-based composite catalyst and a preparation method and application thereof. The manganese-based composite catalyst has excellent long-term stability and is not easy to deactivate.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A metal ion-doped manganese-based composite catalyst, wherein the catalyst is ε-crystal MnO2 doped with metal ions; wherein the metal ions are any one of nickel, cobalt, potassium, sodium, and lithium; and in the catalyst, the molar ratio of manganese element to metal ions is (1-3):1.

[0006] The method for preparing the above-mentioned metal ion-doped manganese-based composite catalyst comprises the following steps:

[0007] S1, dispersing a manganese metal salt and a doping metal salt into deionized water to obtain a mixed metal solution;

[0008] S2. Ozone is introduced into the mixed metal solution, and after the ozone is introduced, the solid and liquid are separated, and then the solution is cleaned, dried and ground to obtain a manganese-based composite catalyst doped with metal ions.

[0009] Preferably, the manganese metal salt is a mixture of one or more of manganese nitrate, manganese chloride, manganese sulfate and manganese acetate.

[0010] Preferably, the doping metal salt is any one of nitrates, sulfates, chlorides and acetates of nickel, cobalt, potassium, sodium and lithium; or a mixture of at least two of nitrates, sulfates, chlorides and acetates of a single metal among nickel, cobalt, potassium, sodium and lithium.

[0011] Preferably, the ozone flow rate is 10-5000 mL / min, the concentration is 1-100 mg / L, and the introduction time is 0.5-3 h.

[0012] Preferably, the drying conditions are: 60-100°C, 6-12h.

[0013] The application of the above-mentioned metal ion-doped manganese-based composite catalyst in catalytic decomposition of ozone includes but is not limited to the decomposition of ozone in the air at room temperature, the removal of ozone on the exterior surfaces of buildings and in motor vehicle radiators, the removal of ozone in confined spaces such as indoors and in high-altitude aircraft, and the removal of ozone in water treatment exhaust gas.

[0014] A method for predicting the catalytic decomposition performance of a catalyst for ozone is to compare the offset values ​​of the diffraction peaks in the XRD spectrum of the metal ion-doped manganese-based composite catalyst and the diffraction peaks in the XRD spectrum of the corresponding ε-crystalline MnO2. The larger the offset value, the better the catalytic decomposition performance of ozone.

[0015] The metal ion-doped manganese-based composite catalyst is ε-crystalline MnO2 doped with metal ions; the metal ions are any one of nickel, cobalt, and potassium; and in the catalyst, the molar ratio of manganese element to metal ions is (1-3):1.

[0016] The beneficial effects of the present invention are:

[0017] The obtained manganese-based composite catalyst has excellent long-term stability and is not easy to deactivate. When doped with K ions and Mn:K=2:1 (molar ratio), the catalyst has the best ozone degradation performance and water resistance. It is at 30°C, RH=60%, 600000mL·g -1 ·h -1 Under the condition of 10 hours, the decomposition efficiency of 50ppm ozone is close to 100%, and the decomposition efficiency is 93.7% after 30 hours, and it remains stable. -1 ·h -1 Under the conditions of 4 hours, the decomposition efficiency of 50ppm ozone is close to 100%. The catalyst shows excellent performance in various harsh environments and is very suitable for ozone decomposition in atmospheric environments.

[0018] Compared with potassium permanganate, ozone has a stronger oxidizing ability, which makes the catalyst have a more complete crystal structure. According to the EPR test results, the catalyst prepared by using ozone has a higher oxygen vacancy concentration, which effectively improves the efficiency of the catalyst in catalyzing the decomposition of ozone. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the X-ray diffraction pattern of the catalysts prepared in Examples 1, 2, 3, 4, 5 and ε-MnO2;

[0020] Figure 2 is the XRD pattern of the catalysts prepared in Examples 1, 6, 7 and Comparative Example 1;

[0021] Figure 3 It is the XRD spectrum of the catalyst prepared in Example 1 and Comparative Examples 1 and 2;

[0022] Figure 4 The catalysts prepared in Examples 1, 2, 3, 4, 5 and Comparative Example 1 were heated at 30°C and at a mass space velocity of 600000 mL·g -1 ·h -1 , performance graph under 60% relative humidity conditions;

[0023] Figure 5 The catalysts prepared in Examples 1, 6, 7 and Comparative Example 1 were heated at 30°C and a mass space velocity of 600,000 mL·g -1 ·h -1 , performance graph under 60% relative humidity conditions;

[0024] Figure 5 The catalysts prepared in Examples 1, 6, 7 and Comparative Example 1 were heated at 30°C and a mass space velocity of 600,000 mL·g -1 ·h -1 , performance graph under 60% relative humidity conditions;

[0025] Figure 6 The catalyst prepared in Example 1 and Comparative Examples 1 and 2 was heated at 30°C and a mass space velocity of 600000 mL·g -1 ·h -1 , performance graph under 60% relative humidity conditions;

[0026] Figure 7 The catalyst prepared in Example 1 and Comparative Examples 1 and 2 was heated at 0°C and a mass space velocity of 600000 mL·g -1 ·h -1 , performance graph under 60% relative humidity conditions;

[0027] Figure 8The catalyst prepared in Example 1 was heated at 30°C and a mass space velocity of 600,000 mL·g -1 ·h -1 , performance graph for 30h under 60% relative humidity;

[0028] Fig. 9 It is the EPR spectra of the catalysts prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0029] In the following examples and comparative examples, the operating steps of the ozone conversion rate experiment are as follows:

[0030] (1) The catalyst was tableted, ground, sieved, and 40-60 mesh particles were taken. The sample was weighed with an electronic balance and filled into a cylindrical quartz reaction tube with an inner diameter of φ7.0 mm. The bed height was 60 cm;

[0031] (2) Turn on the air source, turn on the ozone generator, control the final flow rate to 0.5-1.5 L / min, make the ozone concentration after gas distribution to 100 ppb-100 ppm, and connect the cylindrical quartz reaction tube to the detection system for testing;

[0032] (3) Detect the concentration change before and after the reaction. The concentration before the reaction must reach [O3]in; under the above experimental conditions, the concentration after the reaction is [O3]out;

[0033] (4) Calculate the ozone conversion rate according to the following formula, and keep two significant figures;

[0034] C={([O3]in-[O3]out) / [O3]in}×100;

[0035] C is the conversion rate of ozone, in %;

[0036] [O3]in----ozone concentration at the reaction inlet, in ppm;

[0037] [O3]out---Ozone concentration at the reaction outlet, in ppm.

[0038] Example 1

[0039] The preparation method of the catalyst provided in this embodiment comprises the following steps:

[0040] (1) Take 5 g of manganese sulfate monohydrate and dissolve it in 100 mL of deionized water. Stir it evenly to obtain solution A.

[0041] (2) Add 0.215 g of potassium sulfate to solution A and stir for 15 minutes to obtain solution B.

[0042] (3) Ozone with a flow rate of 1 L / min and a concentration of 1000 ppm was introduced into solution B through an aeration head for reaction at room temperature for 1 hour. The precipitate was then filtered and washed with 500 mL of deionized water until it was neutral, and dried at 80° C. for 8 hours to obtain the catalyst, which was recorded as K-ε-MnO2-0.5.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that in step (2), 3.888 g of nickel sulfate is added, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as Ni-ε-MnO2.

[0045] Example 3

[0046] The difference between this embodiment and embodiment 1 is that in step (2), 4.158 g of cobalt sulfate is added, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as Co-ε-MnO2.

[0047] Example 4

[0048] The difference between this embodiment and embodiment 1 is that in step (2), 0.946 g of lithium sulfate is added, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as Li-ε-MnO2.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 1 is that in step (2), 1.05 g of sodium sulfate is added, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as Na-ε-MnO2.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 1 is that in step (2), the amount of potassium sulfate added is 0.644 g, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as K-ε-MnO2-0.25.

[0053] Example 7

[0054] The difference between this embodiment and embodiment 1 is that in step (2), the amount of potassium sulfate added is 1.933 g, and the other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as K-ε-MnO2-0.75.

[0055] Comparative Example 1

[0056] The difference between this embodiment and embodiment 1 is that in step (2), no metal salt is added, and other conditions are exactly the same as those in embodiment 1. The obtained catalyst is recorded as O3-ε-MnO2.

[0057] Comparative Example 2

[0058] Take 0.845g of monohydrated manganese sulfate in 150mL of deionized water and stir evenly. Then slowly add 10mmol of potassium permanganate to the solution, stir at room temperature for 3h, filter the resulting product, and wash with deionized water until the pH value of the filtrate is neutral. Dry the black powder at 80℃ overnight. The resulting catalyst is recorded as KMnO4-ε-MnO2.

[0059] Crystal structure analysis

[0060] like Figure 1 As shown in the figure, the diffraction peaks at 37.1°, 42.4°, 56.0°, and 66.7° in the XRD spectrum correspond to the (100), (101), (102), and (110) crystal planes, respectively, which are consistent with ε-MnO2 (JCPDS card No. 30-0820). The peaks of ε-MnO2 are consistent with the corresponding card, and the ε-MnO2 doped with other metal ions all have a certain degree of offset, among which the offset angle of K-ε-MnO2 is the largest. The reason for the offset is that the metal ions are doped into the lattice of ε-MnO2, causing its lattice spacing to increase, thereby causing the XRD angle to shift. Except for Na-ε-MnO2 and Li-ε-MnO2, the offset degree of ε-MnO2 doped with other metal ions is consistent with the decomposition efficiency trend. The larger the offset angle, the higher the ozone decomposition performance.

[0061] like Figure 2 As shown in the figure, the diffraction peaks at 37.1°, 42.4°, 56.0°, and 66.7° in the XRD spectrum correspond to the (100), (101), (102), and (110) crystal planes, respectively, which are consistent with ε-MnO2 (JCPDS card No. 30-0820). The shift angle of the diffraction peak increases with the increase of K / Mn ratio, indicating that there are more K + Doping into the lattice of ε-MnO2 increases the lattice spacing. In the XRD images of catalysts doped with different metal ions, it was found that the larger the offset angle of the diffraction peak of the obtained catalyst, the higher its ozone decomposition performance. However, from the XRD images of different K ion doping amounts, it was found that K-ε-MnO2-0.75 with the largest offset angle did not have the best decomposition performance, indicating that this is not the only factor leading to the improvement of ozone decomposition performance.

[0062] like Figure 3As shown. The diffraction peaks at 37.1°, 42.4°, 56.0°, and 66.7° correspond to (100), (101), (102), and (110) crystal planes, respectively, which are consistent with ε-MnO2 (JCPDS No.30-0820). Each diffraction peak of Example 1 has a certain degree of leftward shift. This may be due to the fact that K ions are doped into the lattice of ε-MnO2, which increases its lattice spacing, thereby causing the XRD diffraction peak to shift to the left. In addition, the diffraction peak intensity of Comparative Example 2 is weaker, which is because the oxidizing property of KMnO4 is weaker than that of ozone, resulting in the failure to form a complete crystal structure. In addition, the grain size of the catalyst was calculated by the Scherrer formula, and the results were Comparative Example 1 (101nm) > Example 1 (76nm) > Comparative Example 2 (68nm). The doping of K ions gives ε-MnO2 a smaller grain size, which is also beneficial to the catalytic reaction.

[0063] Performance Analysis

[0064] Figure 4 It shows that at 600000mL·g -1 ·h -1 The ozone decomposition performance of catalysts doped with different metal ions was tested under the conditions of mass space velocity, 60% relative humidity, 30°C, and 50ppm ozone concentration. The catalytic performance of ε-MnO2 can reach 100% ozone removal rate at the beginning of the experiment, but it begins to decline after about 10 minutes of reaction, and stabilizes at about 50% after 4 hours.

[0065] Doping with different metal ions can improve the ozone removal rate of ε-MnO2 to a certain extent. The catalytic efficiency of Na-ε-MnO2 and Li-ε-MnO2 showed a downward trend after 40 minutes of catalysis. The decomposition efficiency of Na-ε-MnO2 remained at about 60% after 4 hours, and the decomposition efficiency of Li-ε-MnO2 remained at about 75% after 4 hours, indicating that doping with Na ions and Li ions has a general effect on improving the performance of ε-MnO2.

[0066] The catalytic efficiency and decreasing trend of Ni-ε-MnO2 and Co-ε-MnO2 are similar, and their decomposition efficiency is maintained at about 92% after 4 hours. Doping with Ni ions and Co ions has a better effect on improving the performance of ε-MnO2. K-ε-MnO2 has the best ozone decomposition performance, with no decreasing trend within 4 hours, and has maintained a decomposition efficiency of 100%. Doping with K ions has the best effect on improving the performance of ε-MnO2. Therefore, K-ε-MnO2 was selected as the object of subsequent research with different doping ratios.

[0067] Since doping with K ions significantly improves the catalytic performance of ε-MnO2, the performance tests of K-ε-MnO2 doped with different K / Mn molar ratios were added. Figure 5 As shown, at 600000mL g -1 ·h -1 The ozone decomposition performance of different K ion doping ratios was tested under the conditions of mass air velocity, 60% relative humidity, 30°C, and ozone concentration of 50ppm. Figure 5 It can be seen that the decomposition efficiency is the highest when the K / Mn molar ratio is 0.5, and it remains at 100% within 4 hours; while the decomposition efficiency decreases with time when the K / Mn molar ratio is 0.25 and 0.75, and the decomposition efficiency is about 85% and 92% after 4 hours, respectively, which is still better than that of ε-MnO2 without K ion doping, indicating that the doping of K ions has a promoting effect on ozone decomposition. In summary, the decomposition efficiency is best when the K / Mn molar ratio is 0.5.

[0068] like Figure 6 As shown, Example 1 completely decomposes ozone during the entire reaction process and has the best ozone decomposition activity and stability. However, the comparative example 1 without K ion doping quickly drops to 50% after 2 hours. The ozone decomposition performance of the comparative example 2 doped with K ions continues to decrease after 2 hours of reaction, and drops to 89% after 10 hours. In summary, Example 1 has the best stability and water resistance.

[0069] In cold and dry areas, catalysts often become deactivated, so the performance of ε-MnO2 and K-ε-MnO2 was tested under low-temperature dry conditions. Figure 7 The figure shows the ozone decomposition efficiency of ε-MnO2 and K-ε-MnO2 with the same K / Mn molar ratio of 0.5 under low temperature drying environment. It can be seen that the decomposition efficiency of ε-MnO2 under low temperature drying decreases to about 82% over time, while the decomposition efficiency of K-ε-MnO2 remains at 100% during the experimental time, so K-ε-MnO2 can still maintain a good decomposition efficiency under low temperature drying environment, indicating that the doping of K ions can effectively solve the problem of reduced performance of ε-MnO2 under low temperature drying environment.

[0070] Since the catalyst needs to be used for a long time in practical applications, the long-term stability test of the catalyst is added. -1 ·h -1 Under the conditions of mass air velocity, relative humidity of 60%, 30℃ and ozone concentration of 50ppm, the long-term decomposition performance of K-ε-MnO2 with a K / Mn molar ratio of 0.5 was tested. Figure 8As shown in the figure, when the reaction was carried out for 12 hours, the reaction efficiency of K-ε-MnO2 gradually decreased from 100% and stabilized to about 93.7%. It is considered that the long-term reaction produced some products that competed with ozone for attachment sites, resulting in a decrease in decomposition efficiency. The subsequent maintenance of about 93.7% indicates that most of the adsorption sites are not occupied and there are still many contact sites. This shows that K-ion doped ε-MnO2 has excellent long-term stability.

[0071] The presence of oxygen vacancies in the catalyst was further confirmed by EPR. Fig. 9 As shown, the signal at g = 2.003 is generally considered to be evidence of the presence of oxygen vacancies. The oxygen vacancy intensity results are as follows: Comparative Example 2 < Comparative Example 1 < Example 1. There is no signal fluctuation in Comparative Example 2, indicating that there are no oxygen vacancies, which is the reason for its poor performance. Example 1 has the highest signal intensity. Increasing the oxygen vacancy concentration is an effective way to improve the catalytic decomposition of ozone by the catalyst.

[0072] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A metal ion-doped manganese-based composite catalyst, characterized in that: The catalyst is ε-crystalline MnO2 doped with metal ions; wherein the metal ions are any one of nickel, cobalt, potassium, sodium, and lithium; and in the catalyst, the molar ratio of manganese element to metal ions is (1-3):

1.

2. The method for preparing the metal ion-doped manganese-based composite catalyst according to claim 1, characterized in that: The steps include: S1, dispersing a manganese metal salt and a doping metal salt into deionized water to obtain a mixed metal solution; S2. Ozone is introduced into the mixed metal solution, and after the ozone is introduced, the solid and liquid are separated, and then the solution is cleaned, dried and ground to obtain a manganese-based composite catalyst doped with metal ions.

3. The method for preparing the metal ion-doped manganese-based composite catalyst according to claim 2, characterized in that: The manganese metal salt is a mixture of one or more of manganese nitrate, manganese chloride, manganese sulfate and manganese acetate.

4. The method for preparing the metal ion-doped manganese-based composite catalyst according to claim 2, characterized in that: The doping metal salt is any one of nitrates, sulfates, chlorides and acetates of nickel, cobalt, potassium, sodium and lithium; or a mixture of at least two of nitrates, sulfates, chlorides and acetates of a single metal among nickel, cobalt, potassium, sodium and lithium.

5. The method for preparing the metal ion-doped manganese-based composite catalyst according to claim 2, characterized in that: The ozone flow rate is 10-5000mL / min, the concentration is 1-100mg / L, and the injection time is 0.5-3h.

6. The method for preparing the metal ion-doped manganese-based composite catalyst according to claim 2, characterized in that: Drying conditions are: 60-100℃, 6-12h.

7. Use of the metal ion-doped manganese-based composite catalyst according to claim 1 in catalytic decomposition of ozone.

8. A method for predicting the performance of a catalyst for catalytic decomposition of ozone, characterized in that: The method is to compare the diffraction peaks in the XRD spectrum of the metal ion-doped manganese-based composite catalyst with the diffraction peaks in the XRD spectrum of the corresponding ε-crystal MnO2. The larger the offset value, the better the performance of catalytic decomposition of ozone. The metal ion-doped manganese-based composite catalyst is ε-crystalline MnO2 doped with metal ions; the metal ions are any one of nickel, cobalt, and potassium; and in the catalyst, the molar ratio of manganese element to metal ions is (1-3):1.

Citation Information

Cited By

  • Microfluidic control-based continuous preparation of metal-doped active manganese, and preparation method and application thereof

    CN121911440A